A qualitative study exploring the perceived self-image and self-esteem of women diagnosed with polycystic ovarian syndrome using body mapping - Hartmann, Laura Anne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.